Carbon Footprint Evaluation of Organization: Case Study of Ground Business Company Limited - Jekpoo, Namthip; Glinrun, Peangpit (Journal of Advanced Development in Engineering and Science, 2023)
An evaluation of the carbon footprint of organization from a road transportation section in a case study of Ground Business Company Limited is investigated in this research that aims to use the result as database to analyze resource utilization and emissions to environment for strategic planning on greenhouse gases reduction in future. Data for this study were collected in 2016. The total carbon footprint of Ground Business Company Limited was 518.63 ton CO2 equivalent. When the survey data were analyzed, it was found that carbon footprint of activity types 1, 2 and 3 were 465.89, 26.90 and 25.84 ton CO2 equivalent, respectively. The carbon dioxide emission in activity type 1, which is the direct emission, presented the most influential activities, 89 percent of the total carbon footprint. The evaluation of global warming potential of organization per person in this representative year was 11.78 ton CO2 equivalent. A guideline for reducing greenhouse gases from the activities which mostly release greenhouse gases emission in the first priority is the change from gasoline and diesel fuel to NGV gas resulting in the reduction of greenhouse gases emission of 15 % and the decrease of fuel costs of 2.424 million per year.